2023
DOI: 10.1177/20406223231168754
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of different noninvasive brain stimulation therapies for recovery of global cognitive function, attention, memory, and executive function after stroke: a network meta-analysis of randomized controlled trials

Abstract: Background: Which noninvasive brain stimulation (NIBS) treatment – transcranial direct current stimulation (tDCS) or transcranial magnetic stimulation (TMS) – is more beneficial for stroke patients’ cognitive rehabilitation is still up for debate. Objectives: Our goal is to provide an overview of the research on the effectiveness and safety of various NIBS protocols. Design: Systematic review and network meta-analysis (NMA) of randomized controlled trials (RCTs). Methods: This NMA compared any active NIBS vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 94 publications
(283 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have shown that non-invasive stimulation of the DLPFC might serve as one innovative treatment approach to enhance functional recovery after stroke, particularly in the cognitive domain. 29 Herein, stimulation effects were more likely to affect memory, attentional and executive 30 than motor functions. 31 One study found that an increased functional connectivity between contralesional DLPFC and mid-ventrolateral prefrontal cortex was linked to better hand function in chronic stroke patients.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have shown that non-invasive stimulation of the DLPFC might serve as one innovative treatment approach to enhance functional recovery after stroke, particularly in the cognitive domain. 29 Herein, stimulation effects were more likely to affect memory, attentional and executive 30 than motor functions. 31 One study found that an increased functional connectivity between contralesional DLPFC and mid-ventrolateral prefrontal cortex was linked to better hand function in chronic stroke patients.…”
Section: Discussionmentioning
confidence: 92%
“…GABA functions as the principal inhibitory neurotransmitter. The lack of GABA in the DLPFC disrupts the balance between neuronal excitation and inhibition, resulting in increased neural activity, potential harm to the brain, and a loss of cognitive function [ 19 , 20 ]. The interconnection between different regions and networks in the brain may help explain the neuronal pathways that are activated during rTMS stimulation.…”
Section: Discussionmentioning
confidence: 99%